Randomization of Left-Right Asymmetry and Congenital Heart Defects: The Role of DNAH5 in Humans and Mice. (November 2019) - Nöthe-Menchen, Tabea; Wallmeier, Julia; Pennekamp, Petra; Höben, Inga M.; Olbrich, Heike; Loges, Niki T.; Raidt, Johanna; Dougherty, Gerard W.; Hjeij, Rim; Dworniczak, Bernd; Omran, Heymut; Amirav, Israel; et al.
Abstract : Background: Nearly one in 100 live births presents with congenital heart defects (CHD). CHD is frequently associated with laterality defects, such as situs inversus, a mirrored positioning of internal organs. Body laterality is established by a complex process: monocilia at the embryonic left-right organizer facilitate both the generation and sensing of a leftward fluid flow. This induces the conserved left-sided Nodal signaling cascade to initiate asymmetrical organogenesis. Primary ciliary dyskinesia originates from dysfunction of motile cilia, causing symptoms such as chronic sinusitis, bronchiectasis and frequently situs inversus totalis . The most frequently mutated gene in primary ciliary dyskinesia, DNAH5 is associated with randomization of body asymmetry resulting in situs inversus totalis in half of the patients; however, its relation to CHD occurrence in humans has not been investigated in detail so far. Methods: We performed genotype/phenotype correlations in 132 patients with primary ciliary dyskinesia carrying disease-causing DNAH5 mutations, focusing on situs defects and CHD. Using high-speed video microscopy-, immunofluorescence-, and in situ hybridization analyses, we investigated the initial steps of left-right axis establishment in embryos of a Dnah5 -mutant mouse model. Results: In patients with primary ciliary dyskinesia carrying disease-causing DNAH5 mutations, 65.9% (87/132) had laterality defects: 88.5% (77/87) presented with situs inversus totalis, 11.5% (10/87) presented with situs ambiguus ; and 6.1% (8/132) presented with CHD. In Dnah5 mut/mut mice, embryonic left-right organizer monocilia lack outer dynein arms resulting in immotile cilia, impaired flow at the left-right organizer, and randomization of Nodal signaling with normal, reversed or bilateral expression of key molecules. Conclusions: For the first time, we directly demonstrate the disease-mechanism of laterality defects linked to DNAH5 deficiency at the molecular level during embryogenesis. We highlight that mutations in DNAH5 are not only associated with classical randomization of left-right body asymmetry but also with severe laterality defects including CHD. Abstract : Supplemental Digital Content is available in the text.